Genetic evaluation and activity of antifungal against clinical isolate Candida albicans biofilms - Braz, Jaqueline Derissi [UNESP]; Pitangui, Nayla de Souza [UNESP]; Yamashita, Caetano Toshiro [UNESP]; Almeida, Ana Marisa Fusco [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Sardi, Janaína de Cássia Orlandi [UNESP] (My University, 2014)
Candida yeasts are common in the oral cavity and can cause candidosis in the presence of predisposing factors, especially diabetes. The manifestation of the disease is related to this set of local factors such as the presence of dental prostheses, salivary pH, salivary flow and tobacco and the ability to form biofilms. Biofilms are specific and organized communities of cells under the control of signaling molecules rather than random accumulations of cells resulting from cell division and frequently are drugs resistance. Aim: The objectives of this study were to determine the genetic patterns of these C. albicans isolates and to evaluate the in vitro activity amphotericin B and caspofungin against C. albicans biofilms. Methods: Microbial samples were collected from subgingival sites and seeded in CHROMagar for subsequent identification of C. albicans by PCR. Genotypes were defined based on the identification of the transposable introns in the 25S rDNA by PCR. Results: In this study, 6 strains were identified as C. albicans and of these, 3 strains were genotype A and 3 were genotype B. The results showed that both amphotericin B and caspofungin exhibited strong antifungal activities against C. albicans biofilm formation and inhibiting the biofilm formation ranging from 70.8 – 95.3% and 77.7 - 88.7%, respectively. The antifungals studied had low inhibitory effect on preformed biofims, ranging from 39.5 - 50.8% for amphotericin B and from 23.1 - 36.9% for caspofungin at the same concentration. The activity of the two drugs was most effective in inhibit biofilm formation.
Keywords: C. albicans; Identification; Biofilm; Caspofungin; Amphotericin B; Resistance